Motivation and Obesity Care - Sanjay Kalra; Komal Chawla; Nitin Kapoor (Journal of the Pakistan Medical Association, 2023)
Motivation is essential to maintain achieved targets in the long-term management of chronic diseases like obesity. Moreover, the role of motivation becomes even more important when the physiological set point tries to act against the achieved targets. In this brief communication the authors propose a rubric that should assist health care professionals in enhancing the quality of their communication skills, improving the delivery of obesity management, and optimizing therapeutic outcomes by helping their patients with obesity to manage their motivation drive. Keywords: Motivation, Obesity setpoint, weight maintenance, Intensive behavioural therapy.